On some climatological aspects of drought in India - CHOWDHURY, A.; ABHYANKAR, V. P. (MAUSAM, 1984)
Based on data from 1875 to 1980, an attempt has been made in this paper to compile and collect drought climatology of India. Only "meteorological drought", i.e., rainfall deficiency exceeding 25 % of the normal has been considered. Frequency of occurrence of drought in different meteorological sub-divisions has been obtained which has been used to determine its recurrence period. Drought has been classified into moderate and severe categories and the probability of occurrence of these types in different sub-divisions computed and discussed. Depending upon the area of the country affected, drought has been further classified into different categories, viz., localised, semi-vast, vast extensive and calamitous, observed frequency of each type determined. Decadal representation of the drought incidence has been obtained and used to predict its occurrence in any 10.year period. The series is also subjected to power spectrum analysis and significant peaks obtained and discussed. Since no rational criteria to define an year as a good or bad monsoon year for the country as a whole exists at present, an objective and pragmatic approach to solve this problem has been attempted. The following two categories were separately adopted to consider a year as a drought year, viz., (i) When the percentage area affected exceeds 20%, (ii) When the area exceeds 25%. Sequences of a drought year or a good monsoon year have been obtained. This has subsequently been examined to obtain probabilities of a drought year following (a) 3 consecutive good years, (b) 4 good years, and (c) 5 good years. Similarly chances of two consecutive years of drought after each of 3, 4 and 5 consecutive got the monsoon years have been determined. These sequencies have also been utilised to find persistence in occurrence of good or bad (drought) monsoon years and subjected to X2-test to determine its statistical significance.